Sistem Penentuan Lokasi Gangguan Pada Jaringan Distribusi 20 KV GI Garuda Sakti Penyulang Panam Dengan Metode Impedansi - Hendri Agustin Sibarani; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Short circuit fault that occur in the distribution network can breakdown of electricity services to consumers. Therefore, the distance of the fault location needs to be known quickly and precisely. The impedance method can be used to estimate the fault location. Short circuit was simulated by using Panam distribution network model with ETAP 12.6 by applying phase to ground, phase to phase and three phase short circuit fault. The fault location was modeled on bus 19, bus 28, bus 43, bus 81 and bus 133. The input data used is the current and impedance of buses and substations from the simulation. From fault location distance calculation resulted the largest error is 0.0851% with 21,207 meters average distance difference for phase to phase fault, 0.0843% with 21,016 meters average distance difference for phase to ground fault, 0.0215% with 5,356 meters average distance difference for three phase fault.Keywords: distribution system, fault location distance, impedance method